2020
DOI: 10.1007/978-3-030-58157-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Collaboration Quality in Face-to-Face Classroom Settings Using MMLA

Abstract: The estimation of collaboration quality using manual observation and coding is a tedious and difficult task. Researchers have proposed the automation of this process by estimation into few categories (e.g., high vs. low collaboration). However, such categorical estimation lacks in depth and actionability, which can be critical for practitioners. We present a case study that evaluates the feasibility of quantifying collaboration quality and its multiple sub-dimensions (e.g., collaboration flow) in an authentic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
(38 reference statements)
0
5
0
1
Order By: Relevance
“…We identified nineteen papers that provided machine learning evidence on the outcome of an MMLA system. The papers cover a wide range of areas including predicting learning retention (Hwang et al, 2011); expertise and academic performance (Chango et al, 2019;Giannakos et al, 2019;Luz, 2013); performance in problem-solving in coding (Mangaroska et al, 2020); in Maths (Ochoa et al, 2013); in collaborative activities (Chejara et al, 2020;; in openended project-based activities (Spikol et al, 2018;; in face-to-face collaborative problem-solving activities (Cukurova, Zhou, et al, 2020) and to predict students' dialogue acts (Ezen-Can et al, 2015) and oral presentation skills (Munoz et al, 2018). More from the teachers perspective, ML was used to process multimodal data to identify teachers' key instructional segments to assess their instruction (Donnelly et al, 2016) and to extract orchestration graphs including teaching activities and their social plane over time (Prieto et al, 2018).…”
Section: Existing Evidence On the Use Of Mmla To Support Educational Outcomesmentioning
confidence: 99%
“…We identified nineteen papers that provided machine learning evidence on the outcome of an MMLA system. The papers cover a wide range of areas including predicting learning retention (Hwang et al, 2011); expertise and academic performance (Chango et al, 2019;Giannakos et al, 2019;Luz, 2013); performance in problem-solving in coding (Mangaroska et al, 2020); in Maths (Ochoa et al, 2013); in collaborative activities (Chejara et al, 2020;; in openended project-based activities (Spikol et al, 2018;; in face-to-face collaborative problem-solving activities (Cukurova, Zhou, et al, 2020) and to predict students' dialogue acts (Ezen-Can et al, 2015) and oral presentation skills (Munoz et al, 2018). More from the teachers perspective, ML was used to process multimodal data to identify teachers' key instructional segments to assess their instruction (Donnelly et al, 2016) and to extract orchestration graphs including teaching activities and their social plane over time (Prieto et al, 2018).…”
Section: Existing Evidence On the Use Of Mmla To Support Educational Outcomesmentioning
confidence: 99%
“…From Etherpad logs, we extracted the number of characters added or deleted by each student in the group. In our prior work, we found that our prototype's simple features (e.g., speaking time, number of characters) were significant in estimating collaboration quality (further details, see Chejara et al, 2020). Figure 3 illustrates a part of CoTrack's dashboard showing speaking time and social network, which we presented to teachers to investigate their decision-making process during CL.…”
Section: Cotrack Dashboardmentioning
confidence: 99%
“…Aunque son múltiples las complicaciones que surgen (e.g., en relación a la recogida, integración, análisis y visualización de datos multimodales), muchos son ya los investigadores trabajando en esta problemática (conocida en inglés como Multimodal Learning Analytics) (Vieira, Parsons & Byrd, 2018;Samuelsen, Chen & Wasson, 2019;Crescenzi-Lanna, 2020;Du et al, 2021). Entre las propuestas existentes podemos encontrar sistemas que proporcionan retroalimentación al alumno sobre sus habilidades de presentación en público que toman como fuente la voz, la posición y el movimiento (Ochoa et al, 2020); herramientas para la regulación de la colaboración basadas en la conversación y el texto co-creado por los alumnos (Chejara et al, 2020); herramientas para evaluar el rendimiento cognitivo utilizando aspectos fisiológicos y faciales (Sharma et al, 2020); y aplicaciones que utilizan sensores de movimiento y posición para dar soporte al aprendizaje en el trabajo, como puede ser el caso de la medicina y la enfermería (Di Mitri et al, 2019;Echeverría et al, 2018). Sin embargo, las soluciones disponibles no son aún asequibles (Crescenzi-Lanna, 2020), no han sido suficientemente evaluadas (Ifenthaler & Yau, 2020) o no son operativas para su uso en la práctica diaria (Vieira, Parsons & Byrd, 2018;Romero & Ventura, 2020;Pargman & McGrath, 2021).…”
Section: Analíticas De Aprendizaje Para Informar La Toma De Decisione...unclassified